Waiting time information in the Italian NHS: A citizen perspective. Issue 8 (August 2020) - De Rosis, Sabina; Guidotti, Elisa; Zuccarino, Sara; Venturi, Giulia; Ferré, Francesca
Highlights: Online presentation of waiting times presented large variation among observed Italian regions. Data disclosure on websites is driven by compliance with the law. Waiting time statistics are not comparable, thus impeding data benchmarking among providers. Readability of waiting times information is low, thus user comprehension is hampered. Citizens cannot use published waiting time information in their healthcare choices. Abstract: Public involvement in the management and communication of waiting times is known to support initiatives to reduce waiting times, as well as increase fairness and promote transparency and accountability. In order to improve transparency and communication to citizens, Italy recently updated the National Regulatory Plan for Waiting Lists (2019–2021), which calls for the disclosure of waiting time information on healthcare provider webpages. This study analyses waiting time information for outpatient visits and digital services available on the institutional website pages of 144 public healthcare organisations in nine regions and two autonomous provinces of Italy. Web pages were analysed both in terms of the available information/services, using a grid, and in terms of the quality of the text using an advanced readability assessment tool (READ-IT). This information was complemented and validated by regional healthcare key informants during research-specific workshops. Waiting time information disclosure, digital services and text readability varied both within and between the regional healthcare systems and organisations. The types and characteristics of waiting time information and statistics vary considerably with a negative impact on their use for benchmarking and their readability and usability for booking purposes. Overall, communication weaknesses due to low harmonization and clarity of information can undermine efforts in effectively informing and involving the public through online waiting time data disclosure.